Sosialisasi Keunggulan Universitas Teuku Umar Bagi Siswa/i di Barat Selatan Aceh (Barsela) - Muzakkir, Muzakkir; Mauliansyah, Fiandy; Fazri, Anhar; Zuhri, Al; Murhaban, Murhaban; Ikhsan, Ikhsan; Farizal, Teuku; Almunawir, Almunawir (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
The urgency of socialization is the participation of the community, individuals and groups to participate together, according to the objectives of the socialization to convey knowledge and information to the public so that they understand and follow according to the wishes of the stakeholders. The socialization of the advantages of Teuku Umar University for students was carried out in order to provide an understanding of the progress and achievements of Teuku Umar University (UTU) after it was declared state by President Susilo Bambang Yudoyono (SBY) eight years ago. This socialization was carried out considering how students received reports on the success of UTU with the best achievements. Participation obtained from the socialization of campus excellence encourages and fosters the desires and talents of students to continue their education at UTU. The completion of the socialization is expected for students to have aspirations and prepare themselves and invite friends to register at UTU. This dissemination was enthusiastically attended by students from South West Aceh (Barsela). The presenter uses the method of communication plus interactive discussion/dialogue and asks several questions to the students. This communication procedure uses infocus and LCD facilities, the strategy is to display material through slides that are presented by showing various UTU excellence programs that have been achieved, as well as showing videos of the successes that have been achieved by UTU as a campus of pride for the people of West South Aceh.